2018
DOI: 10.1029/2018tc005041
|View full text |Cite
|
Sign up to set email alerts
|

(U‐Th)/He Thermochronology and Zircon Radiation Damage in the South American Passive Margin: Thermal Overprint of the Paraná LIP?

Abstract: New zircon and apatite (U-Th)/He data (AHe and ZHe) from the crystalline basement of the South American passive margin in southern Brazil present a wide distribution of Phanerozoic apparent ages, recording its prerift evolution. Its geological significance can be investigated by modeling the influence of the accumulated radiation damages on the measured crystals in its He ages during a long upper crust residence. Despite the presence of a significant fault in the studied area, the samples essentially constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 84 publications
2
15
0
Order By: Relevance
“…The onset of the break-up was approximately coeval with the emplacement of the Paraná-Etendeka flood basalts in the Paraná Basin (Fig. 2: 15, Hueck et al, 2018;Krob et al, 2020;Rocha et al, 2020). Krob et al (2020) combined stratigraphic records and thermochronological data sets to suggest a possible thermal effect of this mantle plume in the intraplate environment adjacent to its emplacement.…”
Section: Post-cambrian Evolution and Existing Thermochronological Datamentioning
confidence: 93%
“…The onset of the break-up was approximately coeval with the emplacement of the Paraná-Etendeka flood basalts in the Paraná Basin (Fig. 2: 15, Hueck et al, 2018;Krob et al, 2020;Rocha et al, 2020). Krob et al (2020) combined stratigraphic records and thermochronological data sets to suggest a possible thermal effect of this mantle plume in the intraplate environment adjacent to its emplacement.…”
Section: Post-cambrian Evolution and Existing Thermochronological Datamentioning
confidence: 93%
“…The red dashed lines in each plot are the best-fit forward models from each location. 16 Lithosphere…”
Section: Cookesmentioning
confidence: 99%
“…The large ZHe temperature sensitivity window makes it possible to constrain more complete and continuous thermal histories, offering an opportunity to bridge the gap between higher and lower temperature methods. Previous studies have relied on this intrasample spread in ZHe dates to investigate a wide range of geologic processes, such as the Proterozoic thermal history of rocks (e.g., [14]), timing of Laramide exhumation [15], and development of the South American passive margin [16]. However, additional studies are needed to further assess the efficacy of this method.…”
Section: Introductionmentioning
confidence: 99%
“…Published data suggest that an important limit between pre-and post-rift cooling and exhumation is located in the Florianópolis region, southern Brazil (Fig. 1), where a very complex thermal history has been reported (Jelinek et al 2003;Karl et al 2013;Hueck et al 2018a). Further south of this region, thermochronometry studies have reported mainly pre-rift Paleozoic cooling phases in southernmost Brazil (Borba et al 2002(Borba et al , 2003Oliveira et al 2016;Machado et al 2019), Uruguay (Kollenz 2015;Hueck et al 2017;Gomes & Almeida 2019) and Argentina (Kollenz et al 2017).…”
Section: Introductionmentioning
confidence: 98%